Pseudocapacitive Co9S8/graphene electrode for high-rate hybrid supercapacitors. (January 2019) - Xie, Bingqiao; Yu, Mengying; Lu, Luhua; Feng, Huazhang; Yang, Yang; Chen, Ying; Cui, Hongda; Xiao, Rubo; Liu, Jian
Abstract: Cobalt pentlandite (Co9 S8 ) has recently emerged as a promising electrode material for energy storage devices. Herein, Co9 S8 /graphene hybrid is rationally synthesized through a facile hydrothermal method. Minor-sized Co9 S8 flakes is finely-deposited on the surface of graphene sheet and an interconnected Co9 S8 /graphene architecture structure is obtained. The electrochemical test results show that Co9 S8 /graphene electrode delivers a remarkable charge capacity of 540 C g −1 within 1 min and 74.5% capacitance is retained within a discharge time of 14 s. A hybrid supercapacitor assembled with Co9 S8 -involved electrode delivers a high energy density of 37 Wh kg −1 at a power density of 170 W kg −1, and 15.3 Wh kg −1 can be maintained even at a high power density of 12 kW kg −1 . The excellent electrochemical performance should be attributed to abundant active sites, enhanced charge-transfer characters and maximized capacitive contribution of Co9 S8 /graphene electrode. Graphical abstract: Cross-linked and robust Co9 S8 /graphene (CoSG) hybrid electrode with remarkable pseudocapacitive features was designed for high-rate hybrid supercapacitors(HSCs). Image 1